Src family-selective tyrosine kinase inhibitor, PP1, inhibits both Fc epsilonRI- and Thy-1-mediated activation of rat basophilic leukemia cells - Amoui, M; Dráber, P; Dráberová, L (European journal of immunology, 1997)
Cross-linking of the surface receptor with high affinity for IgE (Fc epsilonRI) by multivalent antigen/immunoglobulin E complexes, as well as aggregation of Thy-1 glycoprotein by monoclonal antibodies lead in rat basophilic leukemia cells, clone RBL-2H3, to tyrosine phosphorylation of several cellular proteins, followed by a release of secretory components. To investigate the molecular mechanisms of Fc epsilonRI- and Thy-1-mediated transmembrane signaling and to map a step at which they converge into a common secretory pathway, we used a novel Src family-selective tyrosine kinase inhibitor, 4-amino-5-(4-methylphenyl)-7-(t-butyl)pyrazolo[3,4-d]pyrimidine (PP1), and analyzed its inhibitory activity on cell activation. Here we show that in RBL-2H3 cells PP1 demonstrates substrate specificity for a Src family kinase Lyn. In immunocomplex kinase assays in vitro, PP1 inhibited the Lyn kinase activity at nanomolar levels without any effect on Syk kinase activity. However, in RBL cells activated via aggregation of Fc epsilonRI, phosphorylation of both Syk and Lyn kinases was inhibited. Fc epsilonRI- and Thy-1-mediated early (protein-tyrosine phosphorylation) and late (release of beta-hexosaminidase) activation events were similarly affected by PP1. The inhibition was specific for membrane receptor-mediated signaling and was not observed in cells activated by an exposure to pervanadate. The combined data suggest that activation of Lyn is the early activation step at which the Fc epsilonRI- and Thy-1-mediated activation pathways of mast cells and basophils may converge.
Keywords: pyrazoly; Phosphorylation; techniky in vitro; Tumor Cells, Cultured; pyrimidiny; Basophils; fosforylace; src-Family Kinases; krysa rodu Rattus; zvířata; myši; Mice; nádorové buňky kultivované; receptory IgE; Mast Cells; Leukemia, Basophilic, Acute; Thy-1 Antigens; Receptors, IgE; antigeny Thy-1; In Vitro Techniques; akutní bazofilní leukemie; inhibitory enzymů; Rats; mastocyty; Animals; Pyrimidines; Pyrazoles; Enzyme Inhibitors; bazofily; skupina kinas odvozených od src-genu